ENGINEERING EDUCATION: BETWEEN MISSION AND THE STANDARD - Nadezda G. Bagdasaryan (Moscow Polytechnic University, 2016)
Prompt changes of a technosphere impose relevant requirements to all its infrastructure: in this regard, the question of engineering education mission becomes more and more actual. This article considers the main trends defining character and an orientation of engineering activity with relevant requirements to it. The problem of increase of the conflict between a traditional paradigm of engineering education and becoming alternative paradigm rises, and this is the cause of transition to new model of education in which the sociocultural vector forms a basis for understanding of deep world processes.